Innovations in colorectal cancer treatment: trifluridine and tipiracil with bevacizumab for improved outcomes – a review - Rais, Taruba; Riaz, Rumaisa; Siddiqui, Tasmiyah; Shakeel, Amna; Khan, Afsheen; Zafar, Habiba (Frontiers in Oncology, 2024)
Colorectal cancer ranks second in cancer-related deaths throughout the world. At the time of diagnosis, at least 20% of the patients with CRC had already developed metastases. Treating and effectively managing metastatic colorectal cancer remains an unsolved task for the health sector.Research and clinical trials have been done to find the best possible solution for patients diagnosed with metastatic colorectal cancer. The approval of the combination therapy of trifluridine and tipiracil with bevacizumab for previously treated metastatic colorectal cancer (CRC) by the Food and Drug Administration (FDA) is a remarkable breakthrough in CRC treatment. Our goal through this article is to give detailed knowledge about the pathogenesis of CRC, its prevalence, and its clinical features. The review also covers the categorization of colorectal cancer into stages using the TM system. Here, we have also discussed the past medical treatments that have been used for treating mCRC, including the anti-EGFR therapy, aflibercept, ramucirumab, and regorafenib. However, the focus of this document is to assess the combination of LONSURF (trifluridine/tipiracil) and bevacizumab by reviewing the clinical trials and relevant research.